Stratégies technico-commerciales asiatiques - Vuong, Thanh (Études internationales, 1991)
John Foster Dulles, then Secretary of State under the presidency of Eisenhower, once said there are two ways to conquer: by the clash of arms or through the economic control. The motto of the former WWII British SBS Commandos (Special Boat Service)used to be "United we conquer" and the one from the SAS (Special Air Service) used to be "Who dare win ", both of these commando troops or irregulars were in tactical competition framed by strategic cooperation where the light forces overcame heavier and overnumbering forces. Unity and daringness seem to be their secret weapon, but neither so secret nor so exclusive, comparatively to the recipe of tactical competition framed by strategic co-operation and coordination. "Superior numbers on the battlefield are an undoubted advantage, but skill, better organization, and training, and above all a firmer determination in all ranks to conquer at any cost, are the chief factors of success. Half-hearted measures never attain success in war and lack of determination is the most fruitful source of defeat" wrote Anthony Wilden1. The Chinese "Chii" (close to the latin "anima": heart, mind, courage) may be translated to "determination" and not by "energy" as it uses to be with the western obsession and compulsion of matter, energy and big power at the expense of high determination or "Tai Chi". The Chinese "Lii" - though its primal senses are "Law", "Rationality" and "Reason", "Rite" and "Harmony" - may be viewed as "Skill". Here, Asia is the Far East and mainly Japan, the "mother tiger" and her "baby tigers ", namely Korea (South), Hong Kong, Singapore and Taiwan. The ride of the dragon is oriented elsewhere and devastated Viet Nam (the smaller dragon) - by its independence wars and communist insulation and isolation - is not yet in the game. Strategy is both an organizational level of action and a type of action based on disguise, deception, uncertainty, flexibility and adaptation.